Financial behavior of working women in the sandwich generation in Sleman Regency, Yogyakarta, Indonesia - Artanty, Honesty; Sobaya, Soya (Journal of Islamic Economics Lariba, 2024)
IntroductionWomen in the sandwich generation face unique financial challenges, managing intergenerational responsibilities while navigating socio-economic disparities. This study examines the financial behaviors of sandwich generation women in Sleman District, Indonesia, where regional and cultural differences significantly impact financial practices.ObjectivesThis study aims to explore key aspects of financial behavior, including planning, savings, insurance, investments, debt management, and expenditures. The research investigates how these behaviors differ between urban and rural (tourist area) participants and identifies areas for improvement to promote financial resilience.MethodA qualitative descriptive comparative approach was employed. Data were collected through structured questionnaires and semi-structured interviews with 34 participants, divided evenly between urban and rural regions. The analysis focused on identifying patterns and disparities in financial behaviors and contextual influences.ResultsFindings revealed gaps in retirement planning, emergency savings, and investment practices, with urban participants demonstrating better financial literacy and access to formal financial systems. Rural participants relied heavily on informal financial mechanisms and community networks. Insurance uptake was low due to mistrust and limited awareness of Islamic financial products, while debt management reflected strong financial responsibility. Participants also displayed commendable prioritization of essential expenses and charitable giving.ImplicationsThe study highlights the need for targeted financial literacy programs, accessible financial products, and interventions tailored to regional and cultural contexts. Addressing these gaps can empower sandwich generation women to achieve greater financial independence and resilience.Originality/NoveltyThis research integrates gender, regional, and cultural perspectives to provide a nuanced understanding of financial behavior among sandwich generation women. It contributes actionable insights for policymakers and financial institutions to design effective interventions, addressing an underexplored demographic in the literature.